Authority control - Guerrini, Mauro (Firenze University Press, 2003)
The proceedings published here relate to a conference that was proposed to focus on a decisive aspect of cataloguing. Authority control is the process that ensures the formal uniformity of the options selected for access: author, title, institution, subject. Authority control is an operation that integrates the catalogue architecture, contributing to achieve its objectives by addressing the quality of the registration indices. In addition to offering an opportunity for exchange between the leading world experts in the sector, the conference was also designed to make a contribution to the debate on the review of the national cataloguing codes and their possible harmonisation.